Empreendedorismo social e sustentabilidade econômica em ONGs - Mendonça, Cristiane Maria Oliveira (2014)
The social entrepreneurship is an approach that deals with overcoming the limits imposed by the scarcity of resources, by recognizing and exploiting new opportunities and the context in which the Third Sector organizations, such as NGOs, are is characterized by difficulty in getting the resources necessary to develop their activities and projects . Given this, this paper aims to identify how NGOs from Ceará have developed its economic sustainability through social entrepreneurship as a way of continuing their mission. Case studies were conducted in four Ceará NGOs, being observed the usual and innovative actions under the three criteria of economic sustainability in NGOs (non- mercantile, non- monetary and mercantile). Through the use of content analysis as a research technique, came the conclusion that the NGOs from Ceará have developed their economic sustainability through social entrepreneurship primarily through the intensive development of commercial activities related to commercial criteria, both related to customary practices, such as innovative actions and that this has been fully diversified and directly related to the organizational mission, not limited to the context of scarcity of resources. As for the non-commercial economic sustainability criteria, it was found that little has been undertaken in this area, having been noticed wear of the image of these organizations had after exposure of NGOs that used irregularly donations, generated wear and discomfort in their relationship with companies and individuals. As for public resources, only one NGO has established a strategy focused on continuous participation in bids and the pursuit of tax benefits, being considered by NGOs, a resource wrapped in process, overly bureaucratic and consuming. As for the non- monetary criteria, most NGOs have used it as the latest means of capturing future employees, social networks and have gotten great results. Even those who do not use this communication tool for this purpose, can indirectly capture volunteers , as a network of contacts is created where it shares the performed actions and social activities, arousing the interest of society to collaborate.